Edukasi Fasilitasi Pencegahan Penyalahgunaan Narkotik, Psikotropika dan Zat Adiktif Lainnya di Kota Padang - Rizal, Rosiana; Afriyeni, Helmice; abrar, Nurfajri; saputra, Tegar (Jurnal Pengabdian Masyarakat Dharma Andalas, 2025)
This Community Service Activity aims to provide education for the prevention of drugs, provide information about drugs, the dangers of drugs, and facilitate the prevention of drug abuse in Piai Tangah sub-district, Lubuk Begalung sub-district, Ganting Parak Gadang sub-district, Padang city in the form of counseling carried out in 3 stages during 1 month. Starting from the beginning of May until the 2nd Sunday of August 2023, the preparation stage consisting of meetings with related parties, preparation of proposals and site surveys has been carried out. The next stage is implementation, which is the main agenda, including socialization and counseling. From this service activity, it is hoped that the community and environment of Piai Tangah sub-district, Lubuk Begalung sub-district, Ganting Parak Gadang sub-district, Padang city will receive education to avoid drugs and the majority 75% of participants will understand drugs, the dangers of drugs, preventative measures and rehabilitation facilities.